2020
DOI: 10.1111/gwao.12568
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the postfeminist paradox: The case of UK women veterinary professionals

Abstract: This article critically evaluates how highly qualified women veterinary surgeons make sense of their constrained professional career progression in a context of postfeminism. Postfeminism posits that agentic individualism, combined with professional accreditation, generates a meritocratic pathway for career attainment. A dilemma emerges in the form of a postfeminist paradox however, as this rhetoric of opportunity is not translated into a reality of achievement. To make sense of this dilemma, women can either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Commentators and authors of opinion pieces have speculated about whether increasing numbers of women veterinary graduates represent challenges for the profession, linked with difficulties in recruitment outside metropolitan areas, with the relatively low level of remuneration for veterinarians, or with the economic impact of mental health problems ( 53 – 57 ). The ongoing position of women in the veterinary profession has recently been characterized as a post-feminist paradox, an experience of career limitation at odds with a rhetoric of unconstrained opportunity ( 58 ).…”
Section: Veterinary Practice In a Changing World: Being Veterinarians...mentioning
confidence: 99%
“…Commentators and authors of opinion pieces have speculated about whether increasing numbers of women veterinary graduates represent challenges for the profession, linked with difficulties in recruitment outside metropolitan areas, with the relatively low level of remuneration for veterinarians, or with the economic impact of mental health problems ( 53 – 57 ). The ongoing position of women in the veterinary profession has recently been characterized as a post-feminist paradox, an experience of career limitation at odds with a rhetoric of unconstrained opportunity ( 58 ).…”
Section: Veterinary Practice In a Changing World: Being Veterinarians...mentioning
confidence: 99%
“…This is appropriate for studies employing gender as a lens to analyse how gendered power relations, practices, stereotypes and structures shape the choices, experiences and outcomes of STEM women entrepreneurs facing a “double masculinity” penalty (Kuschel et al. , 2020) due to engaging in entrepreneurship, with an associated masculine construction (Ahl, 2006), in a normatively masculine sector (Treanor et al. , 2021a).…”
Section: Trends In the Researchmentioning
confidence: 99%
“…As expected, qualitative research drew upon smaller sample sizes (ranging from nine to forty) to facilitate deeper insights into the influences upon, experiences and outcomes of STEM women entrepreneurs. This is appropriate for studies employing gender as a lens to analyse how gendered power relations, practices, stereotypes and structures shape the choices, experiences and outcomes of STEM women entrepreneurs facing a "double masculinity" penalty (Kuschel et al, 2020) due to engaging in entrepreneurship, with an associated masculine construction (Ahl, 2006), in a normatively masculine sector (Treanor et al, 2021a). Such research advances knowledge and highlights potential interdependencies and relationships worthy of further exploration.…”
Section: Trends In the Researchmentioning
confidence: 99%
“…In a study by Bhatt (2013) female medical doctors who perceive patriarchal and sexist attitudes in their workplaces reported that they work harder to gain the respect of their supervisors and colleagues and are still directed to less prestigious career fields. These highly qualified professional females who are overwhelmed with psychological pressure, will have to either accept the barriers to their career progress or manifest every obstacle that they face but at any choice, there may be negative consequences for their mental health, life, and career satisfaction (Treanor et al, 2021).…”
Section: Gender Discrimination and Career Satisfactionmentioning
confidence: 99%